The Relationship Between Admission Characteristics and Prognosis of Patients Diagnosed with Crush Syndrome After Consecutive Kahramanmaraş Earthquakes - Mehmet Bosnak; Çapan Konca; Emre Kıymık; Mihriban Dağlar; Mehtap Akbalık Kara; Beltinge Demircioğlu Kılıç (Journal of Pediatric Emergency and Intensive Care Medicine)
Introduction: Crush syndrome (CS) is the systemic manifestation of rhabdomyolysis due to prolonged continuous pressure on muscle tissue. We aimed to discuss the clinical and laboratory characteristics of the children who were diagnosed with CS, after the consecutive Kahramanmaraş earthquakes. Methods: Eleven cases followed in the pediatric intensive care unit with the diagnosis of CS were retrospectively evaluated. The patients’ files were scanned in detail. Demographic, clinical, and laboratory data were recorded from the files. Results: The mean age of the patients was 10.45±4.92 years. Seven of the patients were girls and four were boys. Patients were extricated from the rubble between 7 and 48 hours. The mean admission time was 29.9±39.2 hours. Acute kidney injury was present in 9 patients. Renal replacement therapy (RRT) was required in 7 patients. At admission, presence of dark urine, high prism score, high blood uric acid, and lactate levels was associated with the need for RRT. The mean age was significantly higher in the RRT group. Three patients died. The mean lactate and D-dimer levels at admission were found to be significantly higher in patients who died. Conclusion: Our results show that survival is possible in CS cases with effective and timely treatment approaches. Many parameters at the time of admission are associated with the need for RRT and death. We also found that as the time spent under rubble increases, blood D-dimer and creatinine levels increase, and ionized calcium and albumin levels decrease.